Managing ITF Juniors Tennis Tournaments in the Context of Tourism - BANCIU, Alexandru-Nicolae; POPIRLAN, Claudiu-Ionut; COSMA, Germina (Journal of Environmental Management and Tourism, 2021)
Participation in ITF junior’s tennis tournaments combined with unique sports resources can provide extraordinary experiences. The aim of this paper is to analyze how ITF junior’s tennis tournaments experiences could be planned and managed for the tourism purposes from the aspect of tennis academies managers. Results of the analysis conducted in the research indicate that a facility can provide the full spectrum of experiences when it meets the standards of professional tennis. Recommendations suggested by the paper provide new insight on organizing the ITF junior’s tennis tournaments offer in the destination and can be used by players, trainers, parents and tennis academy managers in order to better serve tennis and sports tourism needs.